EFFICACY OF THE IMMUNOSUPPRESSIVE THERAPY AGAINST THE NEPHROTIC SYNDROME AMONG CHILDREN - A.G. Timofeeva; T.V. Sergeeva; T.V. Margieva; T.S. Voznesenskaya; O.V. Komarova; A.N. Tsygin ("Paediatrician" Publishers LLC, 2007)
The researchers evaluated the efficacy of different immunosuppressive medications in case of steroid dependent and steroid resistant variants of the nephrtic syndrome among children: traditional alkylating agents (cyclophosphamide, chlorbutin), cyclosporine and mycophenolate mofetil. Cyclosporine proved to be most efficient in treatment against steroid dependent nephritic syndrome, as the researchers were more often able to cancel the steroids, while the recurrence of the nephritic syndrome developed less often. In the event of the steroid resistant nephritic syndrome, the full/partial remission was achieved among more than 80% patients also treated by cyclosporine. In case of the proliferating forms of the steroid resistant nephritic syndrome, the positive outcome was achieved among all the children under observation, if mycophenolate mofetil and steroids were further applied. Therapy by the conventional alkylating agents (cyclophosphamide, chlorbutin) proved to be less efficient both for the relief from the steroid dependence and persistent remission of the steroid resistant nephritic syndrome. Key words: nephritic syndrome, immunosuppressive therapy, alkylating agents, cyclosporine, mycophenolate mofetil, children.